2008
DOI: 10.1007/s12311-008-0046-8
|View full text |Cite
|
Sign up to set email alerts
|

The Cerebellum Is Involved in Reward-based Reversal Learning

Abstract: The cerebellum has recently been discussed in terms of a possible involvement in reward-based associative learning. To clarify the cerebellar contribution, eight patients with focal vascular lesions of the cerebellum and a group of 24 healthy subjects matched for age and IQ were compared on a range of different probabilistic outcome-based associative learning tasks, assessing acquisition, reversal, cognitive transfer, and generalization as well as the effect of reward magnitude. Cerebellar patients showed inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 62 publications
(74 reference statements)
9
57
0
Order By: Relevance
“…In line with this notion, neuropsychological studies of patients with cerebellar damage have shown impairments of executive functions such as verbal fluency [5,6], error detection [4], verbal working memory [7][8][9] and planning [10], nonmotor associative learning [11,12], memory [13], spatial attention [14,15], linguistic abilities [16] and emotion regulation [17,18]. Functional neuroimaging has corroborated these findings by reliably showing cerebellar activations across a range of cognitive tasks, e.g., requiring covert word generation [19] or focused attention [20] and verbal working memory in particular [21][22][23][24].…”
Section: Introductionmentioning
confidence: 78%
“…In line with this notion, neuropsychological studies of patients with cerebellar damage have shown impairments of executive functions such as verbal fluency [5,6], error detection [4], verbal working memory [7][8][9] and planning [10], nonmotor associative learning [11,12], memory [13], spatial attention [14,15], linguistic abilities [16] and emotion regulation [17,18]. Functional neuroimaging has corroborated these findings by reliably showing cerebellar activations across a range of cognitive tasks, e.g., requiring covert word generation [19] or focused attention [20] and verbal working memory in particular [21][22][23][24].…”
Section: Introductionmentioning
confidence: 78%
“…Apart from its well defined function for training-induced adjustment of movements by integrating sensory feedback (Seidler et al, 2002), it has been suggested that higher-level feedback -such as reward -can reach the cerebellum to be integrated into learning processes (for review see (Ramnani et al, 2004). In line with this hypothesis, Thoma and coworkers (Thoma et al, 2008) reported deficits in reinforcement learning in patients with cerebellar dysfunction. Whereas the cerebellar mossy and and climbing fiber network may be specifically apt to integrate reinforcement signals (Swain et al, 2011), a MRI resting state analysis suggested the cerebellum to be functionally connected with the nucleus accumbens (Cauda et al, 2011), an area known to receive feedback and reward-related signals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, whereas the initial acquisition guided by reward or other feedback stimuli seems to be normal in cerebellar patients, reversal learning or transfer of an acquired response rule to a new task is impaired Ramnani 2008, 2011;Thoma et al 2008). In animal models of cerebellar dysfunction, rule-learning deficits and impaired optimization were similarly observed.…”
mentioning
confidence: 99%